Needs, rights and perspectives in the Birth Care Pathway during COVID-19 lockdown in Italy: the BiSogni Study, an exploratory qualitative research - G. Tambascia; F. Zambri; M. V. Sola; S. Marocco; V. Di Stefano; F. Marchetti; A. Giusti (BMC Public Health)
Abstract Background With the COVID-19 emergency, the provision of healthcare had to be reorganized. Community Health Services for Families of Trieste adopted new methods to ensure continuity of care and the maintenance of the Standards and Good Practices of the Baby Friendly Initiative of UNICEF for the Birth Care Pathway. The aim of the study was to identify the perceived needs of women, couples, caregivers, and health professionals during the COVID-19 pandemic and evaluate new healthcare strategies, identifying weaknesses and strengths, and future developments. Methods This was an exploratory qualitative study, using online Focus Groups (FGs) with mothers, fathers, pregnant couples, grandparents, peer breastfeeding support mothers’ groups, and healthcare professionals (HCPs). The sample was purposeful, selected through the district healthcare network. After obtaining participants’ consent, FGs were recorded and fully transcribed. Transcripts underwent deductive and inductive categorical analysis using Nvivo12 software. Results Ten FGs were conducted with 86 participants. Situations of increased vulnerability were reported by women who experienced significant levels of loneliness during pregnancy, childbirth, and the first months of their child's life. Regarding healthcare pathways, inconsistencies in the information provided by healthcare services emerged, due to the lack of clear national guidelines for managing childbirth during the pandemic. A controversial healthcare practice was the widespread exclusion of partners from antenatal care, prenatal diagnostics, labour, delivery, and postnatal care. After a period of uncertainty and fear experienced by families and HCPs, significant improvements in the organisation of community and hospital services were described. This was aided by telemedicine, which re-established a sense of care and connection. Positive aspects of the lockdown included a major presence of fathers who could work from home, share daily life with their partners, and take care of their children. Conclusions The COVID-19 emergency has reshaped the provision of healthcare, even in the field of childbirth. Innovative methods have proven to effectively address new needs resulting from physical and social distancing. These strategies could promote sustainable organisational approaches for managing childbirth care. Our results highlighted how policies and practices for future healthcare emergencies could ensure adherence to best practices and promote patient’s rights.